Conductive adhesive and its preparation method and application
By micro-crosslinking modification of the conductive adhesive at high temperature, the problems of the LED chips being easily peeled off and resin precipitation under the wire bonding process are solved, and the high-temperature adhesive and humidity resistance of the conductive adhesive are improved, and are suitable for chip mount applications.
Patent Information
- Application Number
- CN202411555293.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-11-04
AI Technical Summary
Under the high-temperature wire bonding process, LED chips are prone to falling off and resin precipitation (Bleed out) problems, resulting in failure of the wire bonding, and the adhesive performance of traditional chip conductive adhesives in high temperature and high humidity environments, affecting the service life of LEDs.
The phenyl epoxy diluent, curing agent and curing accelerator were used for micro-crosslinking modification at medium temperature to prepare conductive adhesives to improve their viscosity, rheology properties and heat resistance, and enhance the high-temperature adhesion and humidity resistance between the chip and the bracket.
It realizes high adhesion force, high cohesive damage degree, excellent humidity and heat resistance at high temperatures, and solves the problems of chips being easily peeled off and resin precipitation under the bonding process. It is suitable for the field of chip mounting conductive adhesives.
Smart Images

Figure CN119060673B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of adhesives, and in particular to a conductive adhesive and a preparation method and application thereof. Background Art
[0002] As a new generation of semiconductor solid-state light-emitting devices, light-emitting diodes (LEDs) are widely used in various lighting and display fields due to their advantages such as high luminous efficiency and long service life. The automated production line of LEDs includes process steps such as solid crystal, wire bonding, packaging, and reliability evaluation. Among them, the wire bonding process is to use metal wires to weld the pads on the LED chip and the bracket at high temperature. If the LED chip and the bracket are not well bonded at high temperature, and the conductive glue has resin precipitation (bleed out) causing insufficient tension at the solder joint, then the wire bonding will fail. Most LED dead lights are caused by welding problems. In order to ensure the stability and high quality of the wire bonding process, it is necessary to ensure that the LED chip and the bracket have good adhesion under high temperature conditions. Therefore, the solid crystal glue must have good high-temperature bonding performance and extremely low resin precipitation. In addition, as the working environment of LED devices becomes more and more complex, the bonding performance of traditional chip conductive glue decreases under harsh conditions such as high temperature and high humidity, resulting in a decrease in the service life of the LED.
[0003] In order to solve this problem, the existing technology usually uses high heat-resistant and low moisture absorption resins to enhance the temperature and humidity resistance and reliability of chip conductive adhesives. For example, bismaleimide (BMI) and polyimide (PI) resins are used, but these resins are mostly solid powders or high-viscosity fluids. The viscosity of the chip conductive adhesives prepared from them is very high, and a large amount of active diluents (about 20~40 wt% of the resin content) is often required to improve the operating performance of the chip conductive adhesive.
[0004] For example, CN109593500A discloses a highly filled epoxy conductive silver glue for LED solid crystal, which is made of the following raw materials in weight ratio: 100 parts of epoxy resin, 20-100 parts of curing agent, 0.1-3 parts of accelerator, 0.5-15 parts of coupling agent, 0-10 parts of fumed silica, 20-200 parts of diluent, and 400-2800 parts of silver powder; the epoxy resin is composed of 70-90 parts of bisphenol A epoxy resin and 10-30 parts of special epoxy resin; the special epoxy resin is one or a combination of multiple of glycidyl ether, glycidyl amine and alicyclic epoxy resin; the conductive silver glue has high thixotropy and good storage stability. However, the low heat-resistant active diluent also reduces the high temperature resistance and bonding performance of the chip conductive glue, and there is a risk of resin precipitation (bleed out), and it is difficult to strike a balance between good operating performance and high temperature bonding strength.
[0005] In summary, how to solve the problem of easy chip falling off and resin precipitation under high-temperature wire bonding process has become a technical problem that needs to be solved urgently by technical personnel in this field. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a conductive adhesive and a preparation method and application thereof. By adopting specific components for micro-crosslinking modification, the compatibility of each component is improved. The prepared conductive adhesive has the characteristics of high high-temperature adhesion, high degree of cohesive failure, and excellent moisture and heat resistance. The problem of easy chip falling off and resin precipitation under the wire bonding process is solved, and the conductive adhesive is suitable for the field of chip mounting conductive adhesive.
[0007] To achieve this object, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a method for preparing a conductive adhesive, the preparation method comprising the following steps:
[0009] (1) mixing a phenyl epoxy diluent, a curing agent and a curing accelerator, heating and cross-linking to obtain a reaction mixture;
[0010] (2) The reaction mixture is uniformly mixed with a multifunctional epoxy resin and conductive particles to obtain the conductive adhesive.
[0011] The present invention adopts phenyl epoxy diluent to improve the viscosity and rheological properties of the conductive adhesive. The epoxy groups in the phenyl epoxy diluent are slightly cross-linked with the curing agent and the curing accelerator at medium temperature to improve the solubility of the components and the problem of resin precipitation. At the same time, the phenyl structure contained in the phenyl epoxy diluent can increase the heat resistance and water resistance of the conductive adhesive. The conductive adhesive preparation method provided by the present invention has a simple process, mild conditions, easy control, and good process adaptability.
[0012] In the present invention, the micro-crosslinking is the crosslinking of some groups in the curing agent and curing accelerator with some groups in the phenyl epoxy diluent. In order to distinguish it from the complete crosslinking in which all groups react, this reaction is called micro-crosslinking.
[0013] Preferably, in parts by weight, the raw materials for preparing the conductive adhesive include 10-35 parts of phenyl epoxy diluent (for example, 12 parts, 15 parts, 18 parts, 20 parts, 25 parts or 30 parts, etc.), 5-12 parts of curing agent (for example, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts or 11 parts, etc.), 0.5-4.5 parts of curing accelerator (for example, 1 part, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts or 4 parts, etc.), 50-85 parts of multifunctional epoxy resin (for example, 55 parts, 60 parts, 65 parts, 70 parts, 75 parts or 80 parts, etc.), and 300-350 parts of conductive particles (for example, 305 parts, 310 parts, 320 parts, 330 parts or 340 parts, etc.).
[0014] The “parts” and “parts by weight” involved in the present invention are all calculated based on solid content and do not include solvents, dispersants, etc.
[0015] Preferably, the phenyl epoxy diluent comprises a monofunctional epoxy compound containing a phenyl group.
[0016] Preferably, the phenyl epoxy diluent comprises a phenyl-containing glycidyl ether.
[0017] Preferably, the phenyl-containing glycidyl ether includes 4-tert-butylphenyl glycidyl ether and / or glycidyl phenyl ether, and more preferably 4-tert-butylphenyl glycidyl ether. When the phenyl epoxy diluent contains a tert-butyl group in its structure, it has a hydrophobic and moisture-resistant effect, and can further improve the moisture and heat resistance of the conductive adhesive.
[0018] For example, the phenyl-containing glycidyl ether of the present invention can be DENACOL EX-146P (Nagase, Japan) having a structure as shown in Formula I, DENACOL EX-141 (Nagase, Japan) having a structure as shown in Formula II, etc., which are well known to those skilled in the art:
[0019] Formula I Formula II.
[0020] Preferably, the phenyl epoxy diluent has a viscosity of 5-200 cps at 25° C., for example, 10 cps, 20 cps, 50 cps, 80 cps, 100 cps, 120 cps, 150 cps or 180 cps, etc.
[0021] Preferably, the curing agent comprises an amine curing agent.
[0022] Preferably, the curing agent includes any one of m-phenylenediamine, 4,4'-diaminodiphenylmethane (DDM), 4,4'-diaminodiphenyl sulfone (DDS) or dicyandiamide, or a combination of at least two thereof.
[0023] Preferably, the curing accelerator comprises a latent curing accelerator.
[0024] Exemplarily, the latent curing accelerator of the present invention can be any one of Ajinomoto PN-23, PN-23J, MY-24, MY-25, 2E4MZ, 2E4MZ-CN, 4-methyl-2-phenylimidazole or 2MA-OK of Shikoku Chemical, or a combination of at least two thereof.
[0025] Preferably, the temperature of the heating cross-linking is 65-95°C, for example, 68°C, 70°C, 75°C, 80°C, 85°C or 90°C, etc., more preferably 70-90°C.
[0026] Preferably, the heating cross-linking time is 0.5-4 h, for example, 1 h, 1.5 h, 2 h, 2.5 h, 3 h or 3.5 h.
[0027] Preferably, the multifunctional epoxy resin comprises a polyaromatic epoxy resin and / or an alicyclic epoxy resin.
[0028] Preferably, the polyaromatic epoxy resin includes any one of bisphenol A epoxy resin, bisphenol F epoxy resin or novolac epoxy resin, or a combination of at least two of them.
[0029] Preferably, the multifunctional epoxy resin comprises a combination of a novolac epoxy resin and an alicyclic epoxy resin.
[0030] Preferably, the mass ratio of the phenolic epoxy resin to the alicyclic epoxy resin is 1:(1-3.5), wherein the specific value of (1-3.5) can be, for example, 1.2, 1.5, 1.8, 2, 2.2, 2.5, 2.8, 3 or 3.2.
[0031] As a preferred technical solution of the present invention, by adopting a specific ratio of phenolic epoxy resin and alicyclic epoxy resin, the high temperature resistance and interface bonding ability of the conductive adhesive are further improved, and the amount of phenyl-containing epoxy diluent added is reduced, so that the epoxy adhesive has both excellent operating performance and high reliability.
[0032] Preferably, the epoxy equivalent of the phenolic epoxy resin is 160-250 g / Eq, for example, 170 g / Eq, 180 g / Eq, 190 g / Eq, 200 g / Eq, 210 g / Eq, 220 g / Eq, 230 g / Eq or 240 g / Eq, etc.
[0033] Preferably, the viscosity of the phenolic epoxy resin at 25° C. is 20,000-65,000 mPa·s, for example, 25,000 mPa·s, 30,000 mPa·s, 35,000 mPa·s, 40,000 mPa·s, 45,000 mPa·s, 50,000 mPa·s, 55,000 mPa·s or 60,000 mPa·s.
[0034] As a preferred technical solution of the present invention, by compounding a phenolic epoxy resin with a specific epoxy equivalent and a specific viscosity with other components, the conductive adhesive is ensured to have excellent processability. When the epoxy equivalent is too large, the resin molecular weight is large, close to a solid state, and difficult to dissolve and disperse, resulting in poor workability of the conductive adhesive. When the epoxy equivalent is too small, although the resin viscosity is reduced, the raw material cost is high, which is not conducive to large-scale commercial applications.
[0035] For example, the phenolic epoxy resin in the present invention may be N770 (DIC of Japan), N740 (DIC of Japan), N730A (DIC of Japan), etc., which are well known to those skilled in the art.
[0036] Preferably, the epoxy equivalent of the alicyclic epoxy resin is 100-190 g / Eq, for example, 110 g / Eq, 120 g / Eq, 130 g / Eq, 140 g / Eq, 150 g / Eq, 160 g / Eq, 170 g / Eq or 180 g / Eq, etc.
[0037] As a preferred technical solution of the present invention, a conductive adhesive with excellent heat resistance and processability is prepared by using a cycloaliphatic epoxy resin with a specific epoxy equivalent. When the epoxy equivalent is too large, the cycloaliphatic epoxy resin is difficult to dilute, and a large amount of diluent still needs to be added to reduce the viscosity, resulting in a decrease in the reliability of the conductive adhesive; when the epoxy equivalent is too small, the cycloaliphatic epoxy resin has low functionality and high reactivity, and the high temperature resistance and room temperature storage performance of the resulting conductive adhesive are poor.
[0038] For example, the alicyclic epoxy resin described in the present invention may be TTA800 (Jiangsu Taitel), UVR6103 (Hubei Xinjing New Materials), 2021P (Japan Daicel), S186 (Hubei Xinjing New Materials), TTA21P (Jiangsu Taitel), TTA26 (Jiangsu Taitel), TTA28 (Jiangsu Taitel), etc., which are well known to those skilled in the art.
[0039] Preferably, the conductive particles include silver particles.
[0040] Preferably, the conductive particles include spherical particles and / or flake particles.
[0041] Preferably, the conductive particles are a combination of spherical silver powder and flaky silver powder, in which case the thermal conductivity of the conductive adhesive is significantly improved.
[0042] The present invention has no particular limitation on the source of the silver powder, and commercially available products known to those skilled in the art may be used, such as EA-0295PH from Metalor, SF-125 from TECHNIC Inc, and KT071 from Toyo Chemical Industry of Japan.
[0043] Preferably, the uniformly mixed raw materials in step (2) further include auxiliary agents.
[0044] Preferably, the weight portion of the auxiliary agent is 0.4-3 parts, for example, it can be 0.5 parts, 0.8 parts, 1 parts, 1.2 parts, 1.5 parts, 2 parts or 2.5 parts.
[0045] Preferably, the auxiliary agent includes any one of a conductive promoter, an adhesion promoter, a thixotropic agent or a colorant, or a combination of at least two thereof.
[0046] Preferably, the conductivity promoter comprises a carboxylic acid compound.
[0047] Preferably, the carboxylic acid compound comprises a dicarboxylic acid and / or a monocarboxylic acid.
[0048] Preferably, the dicarboxylic acid comprises adipic acid.
[0049] Preferably, the monocarboxylic acid includes any one of 5-aminosalicylic acid, tyrosine, 3,5-dihydroxybenzoic acid or 3-hydroxybenzoic acid, or a combination of at least two thereof.
[0050] Preferably, the adhesion promoter includes a silane coupling agent and / or a BYK4511 adhesion promoter.
[0051] Preferably, the uniform mixing is carried out in a double planetary hybrid stirring tank.
[0052] Preferably, after the mixing is uniformly performed in step (2), grinding and degassing are performed to obtain the conductive adhesive.
[0053] Preferably, the grinding is performed in a triple roll mill.
[0054] Preferably, the degassing pressure is ≤-0.095 MPa, for example, it may be -0.1 MPa, -0.12 MPa, -0.15 MPa, -0.2 MPa or -0.25 MPa.
[0055] Preferably, the degassing time is 15-25 min, for example, it can be 16 min, 17 min, 18 min, 19 min, 20 min, 21 min, 22 min, 23 min or 24 min, etc.
[0056] Preferably, the preparation method comprises the following steps:
[0057] (1) mixing 10-25 parts of phenyl epoxy diluent, 5-12 parts of curing agent and 0.5-4.5 parts of curing accelerator, heating at 65-95° C. for crosslinking for 0.5-4 h to obtain a reaction mixture;
[0058] (2) The reaction mixture is first mixed evenly with 50-85 parts of a multifunctional epoxy resin, and then mixed evenly with 300-350 parts of conductive particles and 0.4-3 parts of an auxiliary agent, ground, and degassed at ≤-0.095 MPa for 15-25 min to obtain the conductive adhesive.
[0059] In a second aspect, the present invention provides a conductive adhesive, which is prepared by the preparation method described in the first aspect.
[0060] In a third aspect, the present invention provides a use of the conductive adhesive as described in the second aspect in chip mounting.
[0061] Compared with the prior art, the present invention has at least the following beneficial effects:
[0062] The present invention adopts specific components for micro-crosslinking modification at medium temperature to obtain good overall interaction. The prepared conductive adhesive has both good operating performance and high-temperature adhesion, and excellent moisture and heat resistance. The residual adhesive rate and the chip thrust at room temperature, high temperature and PCT aging are high, which solves the problem of easy chip falling off and resin precipitation in the wire bonding process, and can meet the application requirements in chip mounting. BRIEF DESCRIPTION OF THE DRAWINGS
[0063] Figure 1 The residual adhesive of the conductive adhesive obtained in Example 2 at 260°C;
[0064] Figure 2 The residual adhesive of the conductive adhesive obtained in Comparative Example 2 at 260°C;
[0065] Figure 3 The resin precipitation after curing of the conductive adhesive obtained in Example 2;
[0066] Figure 4 This is the resin precipitation situation after the conductive adhesive obtained in Comparative Example 3 is cured. DETAILED DESCRIPTION
[0067] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. However, the following examples are only simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.
[0068] In the following specific implementations of the present invention, the materials involved are shown in Table 1.
[0069] Table 1
[0070]
[0071] Examples 1-8, Comparative Examples 1-3
[0072] A conductive adhesive, the types and amounts of each component are shown in Table 2 and Table 3, and the units of the amount of each component are "parts by weight";
[0073] The conductive adhesive is prepared by the following method:
[0074] (1) Adding a diluent, a curing agent and a curing accelerator into a stirred reactor, stirring, and performing medium-temperature micro-crosslinking under the conditions shown in Table 2 and Table 3 to obtain a reaction mixture;
[0075] When medium-temperature micro-crosslinking is not performed, the diluent, curing agent and curing accelerator are mixed and then directly mixed with subsequent components;
[0076] (2) Adding a multifunctional epoxy resin to the reaction mixture, stirring and mixing evenly, then adding conductive particles and additives, stirring and mixing evenly, passing through a three-roll mill and degassing at a vacuum degree of ≤-0.095 MPa for 15 min before discharging the material to obtain the conductive adhesive.
[0077] Table 2
[0078]
[0079] Table 3
[0080]
[0081] The conductive adhesives obtained in the examples and comparative examples were tested as follows:
[0082] 1) Chip thrust:
[0083] The Die-Shear Strength test method refers to "HG / T 5912-2021 Conductive Adhesives", the silicon wafer size is: 2mm×2mm; the substrate is a silver-plated copper sheet, the curing conditions are a blast oven at 175℃, 1.0 h; the test equipment is a DAGE-4000P multi-function push-pull test machine, Nordson DAGE Precision Industries LTD, USA, and the shear strength is the thrust size (in kgF); 10 samples of each adhesive are taken, and the average value is taken. When measuring the high-temperature thrust at 260℃, the temperature of the temperature-controlled heating table is set, and after reaching the target temperature, it is stabilized for 5 minutes before starting to measure the thrust.
[0084] 2) Evaluation of chip residual glue rate:
[0085] The residual glue on the substrate after thrust damage was observed under an optical microscope, and the area ratio of the residual glue part (percentage relative to the chip area) was evaluated, and the arithmetic mean value of 10 samples was taken.
[0086] 3) Moisture and heat resistance:
[0087] The chip thrust silicon wafer was boiled in a PCT aging box at the conditions of 16 h, 121°C, and 2 bar water vapor, and then the chip thrust test and residual glue rate evaluation were carried out.
[0088] 4) Evaluation of resin precipitation:
[0089] After the conductive adhesive on the silver-plated copper sheet was cured, it was observed under an optical microscope to measure the size of the resin precipitate (i.e., RBO) around the conductive adhesive.
[0090] The test results are summarized in Table 4.
[0091] Table 4
[0092]
[0093] It can be seen from the test results that the present invention achieves better overall interaction by using specific components for micro-cross-linking modification at medium temperature, thereby producing a conductive adhesive with high high-temperature adhesion and excellent moisture and heat resistance, which solves the problems of easy chip falling off and resin precipitation during the wire bonding process.
[0094] Compared with Example 2, it can be found that when the multifunctional epoxy resin includes a specific combination of phenolic epoxy resin and alicyclic epoxy resin, the chip thrust and residual adhesive rate of the obtained conductive adhesive at room temperature, high temperature and after PCT aging are higher, and there is no resin precipitation.
[0095] Compared with Example 2, it can be found that in the present invention, by adopting a specific combination of flaky silver powder and spherical silver powder, the chip thrust and residual glue rate at room temperature, high temperature and after PCT aging are optimized and improved.
[0096] Compared with Example 1, Examples 5 and 6 show that when the micro-crosslinking temperature is too high, the chip thrust and residual adhesive rate of the obtained conductive adhesive at room temperature, high temperature and after PCT aging deteriorate. This is because the degree of medium-temperature micro-crosslinking in Example 5 is relatively high, which causes the viscosity of the system to increase, thereby reducing the wettability between the chip and the silver-plated frame and poor processability; when the micro-crosslinking temperature is too low, the obtained conductive adhesive resin precipitates severely, affecting the subsequent chip packaging wire bonding process.
[0097] Compared with Example 1, it can be found from Examples 7 and 8 that when the content of phenyl epoxy diluent is too high, the viscosity of the conductive adhesive is low, it is easy to drip, the resin precipitates seriously, and the dispensing operation cannot be performed; when the content of phenyl epoxy diluent is too low, the viscosity of the conductive adhesive is too high, and the dispensing operation cannot be performed.
[0098] Comparative Examples 1 and 3 are compared with Examples 1 and 3. It can be found that without medium-temperature micro-crosslinking treatment, under the same material ratio, the normal temperature and high temperature thrust of the obtained chip are significantly reduced, and the chip residual glue rate is low (such as Figure 1 , Figure 2 As shown in the figure), after PCT wet-heat aging, the thrust attenuation is large and the resin precipitation is serious.
[0099] Compared with Example 3, it can be found that when the phenyl epoxy diluent is replaced by the active diluent n-butyl glycidyl ether, since the active diluent does not contain phenyl, the heat resistance of the curing agent cannot be improved by the medium-temperature micro-crosslinking technology. Therefore, the high-temperature thrust and residual glue rate of Comparative Example 2 are poor, and the moisture and heat resistance is also reduced.
[0100] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a conductive adhesive, characterized in that: The preparation method comprises the following steps: (1) mixing a phenyl epoxy diluent, a curing agent and a curing accelerator, heating and cross-linking to obtain a reaction mixture; (2) uniformly mixing the reaction mixture with a multifunctional epoxy resin and conductive particles to obtain the conductive adhesive; The temperature of the heating cross-linking is 65-95°C; The heating cross-linking time is 0.5-4 h; In parts by weight, the raw materials for preparing the conductive adhesive include 10-35 parts of phenyl epoxy diluent, 5-12 parts of curing agent, 0.5-4.5 parts of curing accelerator, 50-85 parts of multifunctional epoxy resin, and 300-350 parts of conductive particles; The multifunctional epoxy resin includes a combination of a phenolic epoxy resin and an alicyclic epoxy resin; The epoxy equivalent of the phenolic epoxy resin is 160-250 g / Eq; The epoxy equivalent of the alicyclic epoxy resin is 100-190 g / Eq; The curing agent includes an amine curing agent; The curing accelerator includes a latent curing accelerator; The phenyl epoxy diluent includes a phenyl-containing glycidyl ether.
2. The preparation method according to claim 1, characterized in that The phenyl epoxy diluent has a viscosity of 5-200 cps at 25°C.
3. The preparation method according to claim 1, characterized in that: The mass ratio of the phenolic epoxy resin to the alicyclic epoxy resin is 1:(1-3.5); The viscosity of the phenolic epoxy resin at 25° C. is 20000-65000 mPa·s.
4. The preparation method according to claim 1, characterized in that: The conductive particles include silver particles; The conductive particles include spherical particles and / or flake particles.
5. The preparation method according to claim 1, characterized in that: The uniformly mixed raw materials in step (2) also include auxiliary agents; The weight portion of the auxiliary agent is 0.4-3 parts; The auxiliary agent includes any one or a combination of at least two of a conductive promoter, an adhesion promoter, a thixotropic agent or a colorant; The conductive promoter includes a carboxylic acid compound.
6. A conductive adhesive, characterized in that: The conductive adhesive is prepared by the preparation method according to any one of claims 1 to 5.
7. An application of the conductive adhesive as claimed in claim 6, characterized in that: The conductive adhesive is used for chip mounting.
Citation Information
Patent Citations
Highly filled epoxy conductive silver adhesive for crystal curing of LED and preparation method thereof
CN109593500A
Thermoconductive electroconductive adhesive composition
CN106459718A
High-temperature-resistant epoxy resin conductive adhesive and preparation method thereof
CN113372844A